ABDUCTIVE THINKING FOR DESIGN THINKING STRATEGIES IN BUSINESS RESEARCH METHODOLOGY - Viriyasuebphong, Petcharut; Kultangwattana, Petchprakay (RMUTT Global Business and Economics Review, 2021)
The purposes of this research were to conduct studies concerning the previous studies of students. Business Research Regulation Courses from 2013-2019. To develop design thinking skills and separate research data based by abductive learning for students Business Research Regulations. The population used in this research is the population at this time is the research work of students studying business research methodology from 2013-2019. The research instruments used are questionnaire, analysis and document research. Data analysis using the twin diamond model, there are 4 steps: Discover Define Develop and Deliver. The results of the research showed that the majority of documents evaluated were in good quality. There are 34 good quality researches from 56 research works, accounting for 61%. In summary, the evaluation results of first-level researchers and second-level researchers have a complete level of content that can be used for research development. The third level researcher develops design thinking skills in research design. In 2020 resulting in new problems resulting from the synthesis of research in 2 areas as follows: 1) guidelines for the development of personnel, economy and environmental resources of the community, and 2) the decision to buy coffee by consumers.